2016
DOI: 10.4102/ajlm.v5i1.187
|View full text |Cite
|
Sign up to set email alerts
|

Development of immunohistochemistry services for cancer care in western Kenya: Implications for low- and middle-income countries

Abstract: BackgroundCancer is becoming a major cause of mortality in low- and middle-income countries. Unlike infectious disease, malignancy and other chronic conditions require significant supportive infrastructure for diagnostics, staging and treatment. In addition to morphologic diagnosis, diagnostic pathways in oncology frequently require immunohistochemistry (IHC) for confirmation. We present the experience of a tertiary-care hospital serving rural western Kenya, which developed and validated an IHC laboratory in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Moreover, studies have also demonstrated that p16/Ki-67 assay is able to identify accurately women at risk of precancerous lesions who may need to undergo further retesting at extended intervals [31]. Thus, with minimal training on the staining and interpretation protocol as demonstrated earlier in Slovenia and California [65][66][67], other cytotechnologists and cytopathologists in low and middle income countries (LMIC) would equally be able to examine and report correctly cases of cervical neoplasia given that similar trainings had also been piloted in Kenya and Malawi with good results [68]. Furthermore, considering the interobservers variability, and the need for repeat tests associated with Pap cytology, studies have equally shown that implementation of p16/Ki-67 assay would be more cost effective compared to the conventional Pap cytology [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have also demonstrated that p16/Ki-67 assay is able to identify accurately women at risk of precancerous lesions who may need to undergo further retesting at extended intervals [31]. Thus, with minimal training on the staining and interpretation protocol as demonstrated earlier in Slovenia and California [65][66][67], other cytotechnologists and cytopathologists in low and middle income countries (LMIC) would equally be able to examine and report correctly cases of cervical neoplasia given that similar trainings had also been piloted in Kenya and Malawi with good results [68]. Furthermore, considering the interobservers variability, and the need for repeat tests associated with Pap cytology, studies have equally shown that implementation of p16/Ki-67 assay would be more cost effective compared to the conventional Pap cytology [69].…”
Section: Discussionmentioning
confidence: 99%
“…The larger AUC and higher NPV correspond to a better diagnostic tool. Consequently, the reported test performance and the receiving operating characteristics curves implies that implementation of p16ink4a / ki-67 assay as a point of care test to be used specifically to triage HPV-DNA positive women at one visit with subsequent cryotherapy treatment is feasible, especially in regions with inadequate histology infrastructure such as Kenya [68,77]. This will reduce colposcopy referrals [78], and cushion high loss to follow-up associated with histology longer turnaround time [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…[171819] However, IHC staining can be limited by insufficient tissue samples, and in some settings, a lack of resources. [2021]…”
Section: Introductionmentioning
confidence: 99%
“…Another reason is that facilities for immunohistochemical analysis in this centre existed at the latter half of the study period. Also, immunohistochemical stains are still limited and seldom used in most histopathology laboratories in Africa, due to various reasons highlighted in reports by Adeyi ( 4 ) and Patel et al, ( 28 ), with pathologist often relying wholly on histodiagnosis ( 4 , 28 ). Adeyi and Patel et al, in their studies suggested models for the improvement of histodiagnostic services in Africa including mentoring and collaboration with institutions in the developed world ( 4 , 28 ).…”
Section: Discussionmentioning
confidence: 99%